2018
DOI: 10.1007/s00436-018-6172-4
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of South Indian field isolates of bovine Babesia spp. and Anaplasma spp.

Abstract: Ticks and tick-borne diseases (TTBDs) are considered major causes of economic loss in the livestock sector which incur an annual control cost estimated at US$ 498.7 million in India. Among these diseases, babesiosis, theileriosis and anaplasmosis are listed among the top ten livestock diseases in India and cause significant mortality and morbidity among cattle. However, molecular characterization of bovine Babesia and Anaplasma species are scant; thus, the aim of this study is to perform molecular characteriza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 56 publications
2
10
0
Order By: Relevance
“…The genetic polymorphism of Babesia spp. has been reported earlier using sequence information of 18S rRNA gene [1,33,34]. In the phylogenetic tree, the isolates of the present study formed a separate sub clade but clustered with an isolate from Iraq.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…The genetic polymorphism of Babesia spp. has been reported earlier using sequence information of 18S rRNA gene [1,33,34]. In the phylogenetic tree, the isolates of the present study formed a separate sub clade but clustered with an isolate from Iraq.…”
Section: Discussionsupporting
confidence: 77%
“…However, these distinguished itself from South African and American isolates, simulating reports from Kerala [1], wherein the isolates appeared in two different clades. In another study from India [34], close genetic relatedness was observed between B. bigemina isolates from North Eastern India with Argentina and Kenya rather than with China.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…However, using this method, it was difficult to clearly distinguish between A. capra, A. bovis, A. ovis, and A. phagocytophilum, as they are highly similar in terms of their morphological characteristics (Liu et al, 2012;Li et al, 2015;Wei et al, 2017;Lee et al, 2018). It was also difficult to distinguish these agents from other blood pathogenic agents, such as members of the Theileria and Babesia genera (Al-Hosary et al, 2018;Pradeep et al, 2019). Especially when the pathogen load is low, it is difficult to distinguish between these pathogens by microscopic examination.…”
Section: Introductionmentioning
confidence: 99%